Melihat Sistem Pembelajaran Berdasar Negara Belanda (Current Research in Education: Conference Series Journal, 2022)
Education today is an indicator to qualify for learning, especially for an educator. An educator is one of the most important parts of learning resources for students, so an educator must carry out his duties as an educator by established educational standards so that the learning system runs well. The learning system is basically an effort or ways to achieve learning goals by educators and students. The results of the learning of a student have an important effect on the teaching and learning process. Through the learning outcomes that have been passed by students, the ability of students can be known in understanding the material taught by an educator. For educators, the results of learning are an evaluation to make the development of the educators in providing material, especially in teaching so that students in the future will be better and produce good future generations.